2019
DOI: 10.3892/etm.2019.7676
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑877 inhibits cell proliferation and invasion in non‑small cell lung cancer by directly targeting IGF‑1R

Abstract: MicroRNAs (miRNAs/miRs) are frequently differentially expressed in non-small cell lung cancer (NSCLC), and differential miRNAs expression may be closely associated with NSCLC genesis and development. Therefore, an in-depth investigation of the cancer-associated miRNAs that are crucial for NSCLC pathogenesis may provide effective therapeutic targets for patients with this aggressive malignant tumor type. The expression levels and roles of miR-877 have been well studied in hepatocellular carcinoma and renal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Previous studies have reported miR-877-5p expression was distinctly down-regulated and acted as an oncogene in several tumors, including NSCLC. We also provided evidence that miR-877-5p was highly expressed in both NSCLC specimens from our cohort and cell lines, which was consistent with previous ndings 35 . Then, luciferase reporter gene assays assisted in con rming the regulatory role of DNAH17-AS1 in miR-877-5p.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported miR-877-5p expression was distinctly down-regulated and acted as an oncogene in several tumors, including NSCLC. We also provided evidence that miR-877-5p was highly expressed in both NSCLC specimens from our cohort and cell lines, which was consistent with previous ndings 35 . Then, luciferase reporter gene assays assisted in con rming the regulatory role of DNAH17-AS1 in miR-877-5p.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, the expression of miR-877-5p in non-small cell lung cancer and colorectal cancer was also reduced. 22,23 Functionally, miR-877-5p has been proposed to suppress cell growth, migration and invasion in hepatocellular carcinoma. 24 These findings indicate that miR-877-5p acts as a tumor suppressor in LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC), miR-877 is down-regulated, and the recovery of its expression inhibits the proliferation and invasion of NSCLC cells in vitro [23]. In colorectal cancer, the overexpression of miR-877 attenuates the migration, invasion and proliferation of cancer cells, and also inhibits the tumor growth in vivo [24].…”
Section: Discussionmentioning
confidence: 99%